(untitled) (Jurnal Simki Economic, 2023)
The increasing number of insurance policy owners who close their policies or surrender is one of the long-lasting effects of Covid-19. So it is necessary to investigate qualitatively about the things that underlie the decision making of users of private health insurance services to stop paying premiums to close their insurance policies. This study used a qualitative design with an in-depth interview approach to 10 of the best private health insurance service user informants according to Investor 2022 magazine in Indonesia between June - August 2022. Transcripts of all interview results were analyzed using thematic analysis with a theoretical framework approach to planning behavior (TPB). From the three themes it was found that the perception of obstacles is the only thing that underlies the surrender decision by users of private health insurance. Insurance companies should provide several options for premium payment restructuring schemes and product restructuring and easy access to these options so that customers can be persistent in continuing their policies.